รายการบันเทิงสารช่อง TATV ของเคเบิลทีวีทรูวิชั่นส์ - ศันสนีย์ อมาตยกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This qualitative research is focused on various aspects of tourism news convey by TV programs of TATV in cable TV True visions and how to understand approaches of each infotainment programs, as well as to find out the stakeholder’s satisfaction towards programs. Result indicated that 24 programs show 13 tourism information; 1. Tourism statistic 2. Food and beverage 3. Geographic of Tourism attractions 4. Updated tourism news 5. Historical information 6. Local merchandise 7. Tourism policy administration 8. Accommodations 9. Important tourism attractions 10. Tourism activities 11. Tourism tips 12. Traditional and Cultural 13. Safety information for tourism. In addition, there are 5 kinds of infotainment programs; 1. News 2. Talk Show 3. Documentary 4. Lifestyle 5. Variety. Lastly, stakeholders are satisfied with how the tourism news are transmitted because of such diversify, up to date and practical data. However they feel that the infotainment programs format lack diversity and competency of MC is limited. In this connection, stakeholders suggested that programs presentation should be more variety and present more new tourist attractions. Also, advertisement and PR should be emphasized.